Outcomes of experimental infection of calves with swine influenza H3N2 virus - Lei Shi; Yuekun Lang; Sawrab Roy; Zhenyu Shen; Dipali Gupta; Chao Dai; Muhammad Afnan Khalid; William J. Mitchell; Shuping Zhang; Richard Webby; Juergen Richt; Wenjun Ma (mBio, 2025)
ABSTRACT Unprecedented outbreaks caused by the H5N1 highly pathogenic avian influenza virus (HPAIV) among dairy cows in the United States have raised significant concerns. Whether other subtypes of influenza A viruses (IAVs) can infect and transmit in cattle remains largely unknown. Herein, we infected cattle respiratory and mammary gland cells with different IAVs and two groups of Holstein calves intranasally or orally with a swine H3N2 virus to determine their susceptibility. Naive calves were co-housed with infected animals to investigate virus transmission. Results showed that tested swine and avian IAVs could infect cattle primary nasal turbinate and tracheal epithelial cells, as well as immortalized mammary gland epithelial cells and fibroblasts. No obvious clinical signs, including fever, were observed in infected and contact calves, but macroscopic lung lesions were found in necropsied animals in both groups on day 5 post-infection. Viral shedding was detected in three out of four nasally infected calves but not in orally infected or the two groups of contact animals. Interestingly, viral RNA and antigen could not be detected in all tissues from individual necropsied animals from either infection group, but viral RNA and sequences were detected in serum samples of two nasally infected calves on day 7 post-infection, not on other days and in other animals. Additionally, only the nasally infected animals seroconverted. Our results indicate that in addition to H5N1 HPAIV, swine H3N2 virus can infect cattle but does not transmit efficiently among them, suggesting that other subtypes of IAVs could infect and replicate in cattle.IMPORTANCEHighly pathogenic avian influenza H5N1 virus outbreaks in U.S. dairy herds have raised questions about whether other subtypes of influenza A viruses (IAVs) can infect and transmit in cattle. In this study, we investigated the susceptibility and infection of different IAVs in bovine primary and immortalized cells and Holstein calves. Results showed that avian H5N1 and H9N2, and swine H3N2 IAVs could infect beef cattle primary nasal turbinate and tracheal epithelial cells, as well as immortalized mammary gland epithelial cells and fibroblasts. Moreover, the swine H3N2 could infect the calves through intranasal infection, but not through oral infection, despite no obvious clinical signs and efficient transmission being observed. Our results demonstrate that other subtypes of IAVs can infect cattle and might pose threats to public and animal health.